2021
DOI: 10.4194/aquast714
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement of Tumeric (Curcuma longa) Powder: Impact on Haematological and Biochemical Responses in Clarias gariepinus (Burchell, 1822) Fingerlings

Abstract: Dietary supplementation with herbal extract in the diet of fish has been noted to increase aquaculture production through the improvement of immunity and other physiological dysfunctions related to fish health. A feeding trial was conducted to assess the impact of incorporating varied concentrations of turmeric powder (TP) on haematological and biochemical responses in Clarias gariepinus fingerlings. Five test diets were composed as T1 ((control) (basal diet + 0 % TP)), T2 (basal diet + 1 % TP), T3 (basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The findings were similar to those of (Yonar et al, 2019), who found that rainbow trout (Oncorhynchus mykiss) administered dietary curcumin supplementation had higher Hct, Hb, and RBC levels. (Fawole et al, 2020;Anene et al, 2021) found an increase in MCV in Claris gariepinus fed a diet supplemented with pawpaw seed and onion peel powder. The results of (Zare et al, 2021) study showed that garlic powder, at 10 g/kg, raise RBC levels in Eurasian Perch Perca fluviatilis juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were similar to those of (Yonar et al, 2019), who found that rainbow trout (Oncorhynchus mykiss) administered dietary curcumin supplementation had higher Hct, Hb, and RBC levels. (Fawole et al, 2020;Anene et al, 2021) found an increase in MCV in Claris gariepinus fed a diet supplemented with pawpaw seed and onion peel powder. The results of (Zare et al, 2021) study showed that garlic powder, at 10 g/kg, raise RBC levels in Eurasian Perch Perca fluviatilis juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of turmeric on blood and immunological status of Mugil cephalus 10.3389/fnut.2022.1040259 vaccinated with A. hydrophila bacterium has been assessed (174). The immune response of Japanese flounder and Nile Tilapia fingerlings was enhanced when fed a diet supplemented with curcumin (175,176).…”
Section: Immune Stimulant Impact Of Curcuminmentioning
confidence: 99%
“…Some authors [3,20] reported that fish feed constituents play a vital role in promoting the development and commitment of fish growth and survival rate. Amongst the essential elements (K, Ca, Na, Mg, P) mg/100 g, minerals play important roles in osmoregulation, intermediate metabolism, and skeleton and scale formation lall.…”
Section: Nutrient and Mineral Compositionsmentioning
confidence: 99%
“…Aquaculture occupied the major principal cost in fishery aquaculture with its' sustained advancement in culturing of fishes and shellfish species. Thus, the fastest growing industry with an annual production capacity of 800 million tons [3]; and an annual estimated growth rate of 30 % per year [3,4]. Fish are good source of protein, fatty acids, vitamins, minerals and essential micronutrients as they are one of the major sources of cheap and relatively affordable animal protein sources in Nigeria; constituting about 40 % of animal protein in the diet [5].…”
Section: Introductionmentioning
confidence: 99%